The Impact of Pandemic on the Market Vendors at Brgy. Sta Monica Market: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The pandemic impacts everyone in the Philippines, especially small companies and market vendors. The government declared a national emergency to halt the coronavirus from spreading. Governments agreed to block borders in reaction to the pandemic to slow the virus's spread and prevent too many people from becoming sick. This endeavour aimed to save countless lives while preventing the healthcare system from crumbling. Market merchants, whose livelihood depends on public space and social interaction, suffered a significant setback due to COVID-19. Curfews curtailed their working hours, traffic, and public transit, resulting in lower revenues. To live, many people turned to breaking the law. According to the survey, market vendors believe that the pandemic is causing problems in their lives, and most agree with that statement. The results indicate that the majority of them desire to implement our recommendations.
Keywords: impact of pandemic; Market Vendors